The role of communication technology tools in enhancing job performance among professionals in the telco industry / Mohd Hafiz Sufyan and Ahlam Abdul Aziz - Sufyan, Mohd Hafiz; Abdul Aziz, Ahlam (UiTM Cawangan Negeri Sembilan, 2023)
Communication technology is crucial for projecting a positive image, being competitive, and maintaining a company's market reputation. The TAM (Technology Acceptance Model) is a theoretical paradigm that explains how humans embrace and use technology. According to the concept, individual perceptions of a technology's ease of use and utility are primary drivers of its acceptance. To carry out their jobs, professionals in the telecommunications business may use a variety of communication technologies, such as email, instant messaging, video conferencing, and collaboration tools. Acceptance of these communications’ technology may have a significant impact on job performance since they promote internal communication and cooperation, boost productivity, and allow for remote work. The goal of this study is to investigate the relationship between acceptance of communication technology and job performance among telecommunications professionals. As a result, this study incorporates two key components of technology acceptance model (TAM): perceived usefulness (PU) and perceived ease-of-use (PE) (PEU). This study employed the quantitative method, which comprised an online based questionnaire given to telecommunications professionals. According to the research, the use of communication technology has a substantial effect on job performance. As a consequence, the findings of this study may be applied to increase employee performance on a daily basis.